Pemodelan Run – up Tsunami di Wilayah Pesisir Pantai Sulawesi Barat - Erwan Susanto; Inna Nurana; Akbar Rian Setyahagi (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2020)
The terriotory of Indonesia has a complex tectonic arrangement, making it prone to earthquakes. Earthquakes are one of the biggest factors causing tsunamis. The coastal area of ​​the West Sulawesi coast has a high level of danger from earthquakes and tsunamis because it is close to the Makassar Rise Fault, which is one of the active faults in the West Sulawesi region. From the above background, the writer will conduct research on tsunami run-up modeling in the coastal area of ​​the West Sulawesi coast. The data used in this research are tsunami generator fault parameter data, bathymetric data from GEBCO (General Bathymetric Chart of The Ocean) and SRTM Digital Elevation Medel (DEM) topography data. In this modeling using the help of the TUNAMI – N2 software. The results of this modeling indicate that the maximum run – up in the coastal area of ​​the West Sulawesi coast reaches 11.75453 meters at the observation point of Cinoka Mamuju Utara Port.